Survey of the long term incidence of osteonecrosis of the hip and adverse medical events in rheumatoid arthritis after high dose intravenous methylprednisolone. Issue 11 (November 1988) - Williams, I A; Mitchell, A D; Rothman, W; Tallett, P; Williams, K; Pitt, P
Abstract : A prospective, randomised, double blind, matched cohort survey using retrospective data was undertaken to assess the long term incidence of osteonecrosis of the hip and adverse medical effects occurring after intravenous pulsed methylprednisolone used in the treatment of rheumatoid arthritis over the period 1977-86. One hundred and forty three patients were matched for age, sex, duration and severity of the disease, erosive and serological status. Information was obtained by direct questioning and from hip x rays, the latter being read independently by two 'blind' radiologists. Two definite cases of osteonecrosis were identified, one in both the treated and control groups and three possible cases (radiological disagreement) in the treated group. Adverse medical events, when analysed by systems, were similar in both groups. This study did not provide evidence of increased osteonecrosis of the hip or adverse medical events in the treated group compared with the control group.